Estudio geológico estructural de la galería principal de acceso y transporte, denominada "Mina a la carretera" del área minera "Miranda alto" código 481 del cantón Zaruma provincia del El Oro-Ecuador. - Ordóñez Tandazo, Carla Cristina (2016)
The present project is currently routed to the "Structural Geological Survey of the Main Gallery of access and transportation, called" Mine to the road "the Mining Area" Miranda Alto "Code 481 of the Canton Zaruma province of El Oro-Ecuador". At the first stage, a technical visit was performed to develop a superficial topographical survey of the whole mining area at scale 1: 1500, using topography equipment such as S6 Total Station, yard/meter and GPS; which enabled to obtain a precise uprising of the place. Subsequently, the uprising was conducted underground from the entrance of the mine through the end of the main gallery, taking into account parameters such as width, height and length. Once obtained the topographical characteristics of the area and gallery, the surficial geology was conducted, taking into account the most outstanding outcroppings the place and the- geological map of Zaruma, managing to delimit and establish the geology of the mining area. For performing the structural uprising of the gallery, there were taken into account stations every 10m managing to generate data from the lithology and structures as faults, joints fractures, contacts among others. In the characterization of the massif were taken into account 4 significant sectors depending on the degree of alteration of the massif, performing meshes of 1m x 1m, for the determination of the existing cracks and thus to obtain a volumetric count; information was also generated like the state of cracks, and phreatic water in the area, direction, steeply dipping, frequency or spacing of the boards, degree of openness or gap (open or closed), extension, persistence, continuity, roughness or surface texture (polished, smooth or wrinkled) and filling (with or without filling, type of filler); whereby the structural geology and massif valuation was obtained thus achieving to determine the stability of the place.